Overview of the Biological Activities of Pyrimido[4,5-d]pyrimidines - Cruz, Jacqueline S.; de Aguiar, Alcino Palermo (Mini Reviews in Medicinal Chemistry, 2021)
Over the years, the development of bioactive heterocycles has aroused the interest of the scientific community, because in general, these heterocycles are strategic in maintaining life. Research into bioactive heterocycles is associated with the development of methods of synthesis and the biological evaluation of different nuclei. In consequence, there has been a growing interest in the nucleus of fused pyrimidine, which has diversified pharmacological activities, including diuretic, antimicrobial, antifolate, tyrosine kinase, anti-inflammatory, anticancer, anthelminthic, and antiviral activities. This review focuses on describing a diverse set of structures derived from pyrimido[4,5-d]pyrimidines and contemplates the main bioactivities of these nuclei.
Keywords: diuretic